From friends to romantic partners: an exploration of non-arranged romantic relationship development among urban young adults in India - Dharnidharka, Prerana (Kansas State University, 2014)
The majority of scholarship on romantic relationship development in emerging adulthood is with Western populations using theories grounded in a Western cultural context. This study had two goals. The first goal was to explore the experience of non-arranged romantic relationships for young people in urban India through in-depth interviews with four men and four women. The second was to examine the relevance of Western notions of emerging adulthood, romantic relationship development, and theoretical constructs related to relationship development (e.g., terms such as ‘dating’, ‘commitment’ and ‘satisfaction’) for this population. Findings indicated one potential pathway to relationship formation that begins in friendship and gradually evolves into a romantic relationship. Other findings shed light on young adults’ culturally bound negotiation with their families around the issue of romantic relationships and the similarities in definitions of relationship terms with Western literature. This study makes important contributions to the growing field of romantic relationships in emerging adulthood by suggesting that, first, while Indian youth display several characteristics of emerging adulthood and define commitment similarly as in the West, there are important differences too. Second it has implications for future quantitative measurement of romantic relationships among Indian young adults.
Keywords: young adults, romantic relationships, India, dating, emerging adulthood; Psychology (0621)